Near-Death Experience Memories Include More Episodic Components Than Flashbulb Memories - Cassol, Helena; Bonin, Estelle A. C.; Bastin, Christine; Puttaert, Ninon; Charland-Verville, Vanessa; Laureys, Steven; Martial, Charlotte (Frontiers in Psychology, 2020)
Memories of near-death experiences (NDEs) are recalled as "realer" than memories of other real or imagined events. Given their rich phenomenology, emotionality and consequentiality, it was hypothesized that they could meet some aspects of the definition of flashbulb memories. We aimed to identify and compare the episodic and non-episodic information provided in verbal recollections of NDE, flashbulb and control autobiographical memories. The phenomenological characteristics and centrality of the memories were also compared. Twenty-five participants who had lived a NDE in a life-threatening situation were interviewed and completed the Memory Characteristics Questionnaires as well as the Centrality of Event Scale for their NDE, a flashbulb and another autobiographical memory used as control. Overall, transcribed NDE verbal recollections included a higher overall amount of details and more internal/episodic information than control autobiographical and flashbulb memories. Moreover, flashbulb memories were associated to a lower intensity of feelings while remembering and a lower personal importance, and are less reactivated and less susceptible to be remembered from a first person perspective compared to NDE and control autobiographical memories. Finally, NDE memories are the most central memories to experiencers’ identity, followed by control autobiographical and then by flashbulb memories. These findings corroborate previous studies highlighting the impact and uniqueness of NDE memories.